2012
DOI: 10.1146/annurev-ecolsys-110411-160411
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Community Assembly through the Lens of Coexistence Theory

Abstract: Although research on the role of competitive interactions during community assembly began decades ago, a recent revival of interest has led to new discoveries and research opportunities. Using contemporary coexistence theory that emphasizes stabilizing niche differences and relative fitness differences, we evaluate three empirical approaches for studying community assembly. We show that experimental manipulations of the abiotic or biotic environment, assessments of trait-phylogeny-environment relationships, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
1,161
3
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,158 publications
(1,257 citation statements)
references
References 129 publications
22
1,161
3
17
Order By: Relevance
“…0.15), and did not influence how these variables responded to biogeographic history or phylogenetic distance. The presence of an effect would have indicated that certain environments cause species to overlap more or less in resource use (affecting stabilizing differences) or to have stronger or weaker competitive asymmetries (affecting fitness differences [37]). Instead, the varied responses observed across species pairs likely reflect species-specific differences in responses to soil moisture limitation [26]; in a dry environment, for example, some species pairs might experience more overlap in resource use, whereas others might experience less overlap.…”
Section: Resultsmentioning
confidence: 99%
“…0.15), and did not influence how these variables responded to biogeographic history or phylogenetic distance. The presence of an effect would have indicated that certain environments cause species to overlap more or less in resource use (affecting stabilizing differences) or to have stronger or weaker competitive asymmetries (affecting fitness differences [37]). Instead, the varied responses observed across species pairs likely reflect species-specific differences in responses to soil moisture limitation [26]; in a dry environment, for example, some species pairs might experience more overlap in resource use, whereas others might experience less overlap.…”
Section: Resultsmentioning
confidence: 99%
“…This mixed evidence has led to numerous critiques of the use of phylogeny as a proxy for the processes of community assembly (e.g., Mayfield and Levine 2010, Araya et al 2012, HilleRisLambers et al 2012, Pavoine et al 2013). …”
Section: Accepted Ar Ticlementioning
confidence: 99%
“…Although the former bases the dominance of species on their hierarchy of trait attributes (Kunstler et al 2012;Fort et al 2014), the latter bases species coexistence on the absolute difference between species trait attributes (MacArthur and Levins 1967). Related to these two processes, most recent theories define, respectively, two kind of traits for species coexistence: the ones that promote the difference in species fitness ("fitness difference trait") and the ones that promote the stabilization of niche differences and species coexistence ("niche difference trait") (Levine and HilleRisLambers 2009;Mayfield and Levine 2010;HilleRisLambers et al 2012).…”
Section: Scaling Up From Species Strategies To Species Abundancementioning
confidence: 99%